2021
DOI: 10.35848/1347-4065/ac328f
|View full text |Cite
|
Sign up to set email alerts
|

Growth of twin-free cubic In2O3(111) thick layers on c-plane sapphire substrates by halide vapor phase epitaxy

Abstract: The growth of twin-free single-crystal cubic-indium oxide (c-In2O3) layers was investigated by halide vapor phase epitaxy on c-plane sapphire substrates with various off-axis angles. The growth rate of the c-In2O3 layer increased and twin formation was suppressed as the off-axis angle of the substrate was increased. A single-crystal c-In2O3(111) layer grown on a sapphire substrate with a 5° off-axis angle showed a room temperature carrier density and mobility of 1.4 × 1016 cm−3 and 232 cm2 V−1 s−1, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…This is mainly affected by optical phonon scattering as well as nondegenerated c-In 2 O 3 films. 21,31) The highest Hall mobility of 686 cm 2 V −1 s −1 was observed at 100 K. However, this is also influenced by the SEAL. We can expect to obtain better electrical properties, with regard to both carrier concentration and Hall mobility, through the reduction of the SEAL carriers, for example, by using additional oxygen plasma treatment.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…This is mainly affected by optical phonon scattering as well as nondegenerated c-In 2 O 3 films. 21,31) The highest Hall mobility of 686 cm 2 V −1 s −1 was observed at 100 K. However, this is also influenced by the SEAL. We can expect to obtain better electrical properties, with regard to both carrier concentration and Hall mobility, through the reduction of the SEAL carriers, for example, by using additional oxygen plasma treatment.…”
Section: Discussionmentioning
confidence: 93%
“…c-In 2 O 3 has been grown using various growth methods, such as pulsed laser deposition, 10) molecular beam epitaxy (MBE), [11][12][13] metalorganic chemical vapor deposition, [14][15][16] melt-growth 17,18) and halide vapor-phase epitaxy (HVPE). [19][20][21] Goto et al reported the superior electrical properties of the lowest carrier concentration of 1.4 × 10 16 cm −3 and the highest Hall mobility of 232 cm 2 V −1 s −1 at room temperature in the as-grown c-In 2 O 3 film by HVPE, 21) in which the bulk region is expected to be in a non-degenerate state. Bierwagen et al demonstrated elimination of the surface electron accumulation layer (SEAL) by oxygen plasma treatment in MBE-grown c-In 2 O 3 films.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these substrates are not commercially available and studies of the heteroepitaxial growth of In 2 O 3 on foreign substrates are needed. Numerous groups have attempted to grow c-In 2 O 3 by MBE, [47][48][49] pulsed laser deposition, 50,51) metalorganic CVD, 52,53) HVPE, 9,54,55) and low-pressure CVD. 56) c-In 2 O 3 has also been studied in applications such as Schottky barrier diodes.…”
Section: )mentioning
confidence: 99%
“…In addition, the high-rate growth of c-In 2 O 3 using a non-hydrogenous HVPE system has been demonstrated based on the results of thermodynamic analyses. 9,55) We recently reported that β-Ga 2 O 3 growth by MBE can be explained by thermodynamics, and we assessed the growth mechanism in detail. 58) However, thermodynamic analyses of α-Al 2 O 3 and c-In 2 O 3 growth by MBE have not yet been reported despite the MBE growth of group-III sesquioxides being a topic of interest to many researchers.…”
Section: )mentioning
confidence: 99%